Juvenile polyposis syndrome and hereditary haemorrhagic telangiectasia caused by the SMAD4 gene mutation in a paediatric patient – a case report and a review of the literature - Kaps-Kopiec, Dominika; Pławski, Andrzej; Badura-Stronka, Magdalena; Teisseyre, Mikołaj; Dądalski, Maciej; Cielecka-Kuszyk, Joanna; Pawłowska, Joanna (Pediatria Polska - Polish Journal of Paediatrics, 2021)
Germline mutations in the SMAD4 gene cause juvenile polyposis syndrome and hereditary haemorrhagic telangiectasia. In some cases, the coexistence of these 2 syndromes can be observed among probands with the mutation in the SMAD4 gene. A combined syndrome of juvenile polyps of the gastrointestinal tract and hereditary haemorrhagic telangiectasia caused by mutations of the SMAD4 gene is recognized as a distinct disease entity (OMIM #175050). Herein we present a case of a teenage boy with an affected family history, who was admitted to our department in order to broaden the diagnosis of the causes of his rectal bleeding and recurrent nasal bleeding. In the course of investigation polyps in his gastrointestinal tract and arteriovenous malformations in his lungs were revealed.